And the witnesses were silent : the Confessing Church and the persecution of the Jews - Gerlach, Wolfgang (University of Nebraska Press, 2000)
An endlessly perplexing question of the twentieth century is how "decent" people came to allow, and sometimes even participate in, the Final Solution. Fear obviously had its place, as did apathy. But how does one explain the silence of those people who were committed, active, and often fearless opponents of the Nazi regime on other grounds-those who spoke out against Nazi activities in many areas yet whose response to genocide ranged from tepid disquiet to avoidance? One such group was the Confessing Church, Protestants who often risked their own safety to aid Christian victims of Nazi oppression but whose response to pogroms against Jews was ambivalent